2016
DOI: 10.1155/2016/9075206
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphate Using Red Mud: An Environmentally Hazardous Waste By-Product of Alumina Industry

Abstract: The industrial waste, bauxite residue generated in the Bayer chemical process of alumina production, commonly known as red mud (RM) has been used as the adsorbent for selective removal of phosphate in aqueous solutions. RM collected from the storage area of alumina industry was characterized by chemical analysis and physical methods such as BET surface area, Scanning Electron Microscopy (SEM), particle size analysis, and X-ray diffraction (XRD) methods. Among the various red mud samples (0.2-200 ) studied, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Besides, the results of the physical properties analysis of M-ARM materials by the BET method were described in detail in Table 1. [18]; and (iii) the work of Li et al reported that the best pH value for phosphorus adsorption by RM was 7 [19]. From the above statements, there are some differences which, in our opinion, may be due to different RM activation methods.…”
Section: Resultsmentioning
confidence: 76%
“…Besides, the results of the physical properties analysis of M-ARM materials by the BET method were described in detail in Table 1. [18]; and (iii) the work of Li et al reported that the best pH value for phosphorus adsorption by RM was 7 [19]. From the above statements, there are some differences which, in our opinion, may be due to different RM activation methods.…”
Section: Resultsmentioning
confidence: 76%
“…Experiment results (Figure 8) further show that chemical treatment can considerably improve the adsorption capacity of raw activated carbon [39]. It also seen that up to 50mgL -1 of initial concentration (at Ce 30) it forms monolayer shown in graph but further more increasing nickel concentration, pressure of adsorption increases due to this it starts again adsorption in porous holes.…”
Section: Adsorption Isotherms Studymentioning
confidence: 71%
“…The XRD profiles of the fresh RM, RM-800, and RK-800 catalysts with K doping of 5% to 40% are shown in Figure a. Different crystalline phases found in the fresh RM sample were Fe 2 O 3 (at 2θ of 33.0°, 35.68°, 40.7°, 49.23°, 53.9°, 62.2°, and 64.9°), Al­(OH) 3 (2θ of 18.42°), SiO 2 (2θ of 37.6°), TiO 2 (2θ of 24.4°), and NaAlO 2 (2θ of 20.7°). As reported in our earlier study, calcination of RM at 800 °C resulted in considerable increase in the surface concentration of Fe 2 O 3 and decrease in concentration of active NaAlO 2 , which resulted in low activity of the catalyst. It can be seen from Figure a that KNO 3 remained in well-dispersed phase on the surface of the RM at a lower percentage of K loading (5% to 15%), due to which there were no distinct XRD peaks of KNO 3 observed and Fe 2 O 3 remained as a dominant phase in the RK-800 catalysts loaded up to 15% K. This could be a reason for the low activity of the catalyst at low K loading.…”
Section: Resultsmentioning
confidence: 99%